(untitled) (Research, Society and Development, 2021)
Social Innovation has its field based on the creation of solutions in face of social needs, driven by several agents that organize themselves under the most different legal types, expanding the action of Social Innovation (SI) from a local to national or international field. These social changes impose challenges for managers who start to consider SI as a new dimension for strategy and planning in organizations, requiring the elaboration of future scenarios. The aim of this study was to develop prospective scenarios for social innovation in the short-term. The approach is qualitative and quantitative, using Evidential Annotated Paraconsistent Logic (Et logic). A questionnaire was prepared, containing 58 questions, 57 of which were closed and 1 was open. In order to validate the questionnaire a priori, 3 specialists were consulted, the proposals were confirmed through Delphi rounds and an internal consistency test measured by Cronbach’s Alpha. The sample consisted of 26 participants, distributed in two groups, group A formed by 13 specialists and group B by 13 professional managers or who have participated in social projects. To measure whether there is a statistically significant difference between the groups, the Levene test was used. The results indicate that there is no significant difference between the groups and validate the short-term models, which contain the factors distributed in transformation, innovation, geography of innovation, actors and processes.